The structure Biology and Application of Phytohemagglutinin (PHA) in Phytomedicine: With special up-to-date references to lectins - Movafagh, Abolfazl; Ghanati, Kiandokht; Amani, Davar; Mahdavi, Seyed Mohammad; Hashemi, Mehrdad; Zare Abdolahi, Davood; Darvish, Hossein; Gholami, Milad; HaghNejad, Leyla; Mosammami, Sara; Safari, Shamsi; Darehgazani, Reyhaneh; et al. (Archives of Advances in Biosciences, 2013)
Lectins first discovered more than 100 years ago in plants, they are now known to be present throughout nature. Phytohemagglutinin (PHA), the lectin extract from the red kidney bean (Phaseolus Vulgaris), contain potent, cell agglutinating and mitogenic activities. They play a role in biological recognition phenomena involving cells and proteins towards medical applications. The present article is a brief review of the history of lectin in nature. By reviewing the web-based search for all types of peer review articles published, was initiated using ISI web of Sciences and Medline / PubMed, and other pertinent references on websites about lectins. Here, we present a brief account of 100-plus years of lectin research and show how these proteins have become the focus of intense interest for biologists and in particular for the research and applications in medicine. Phytohemagglutinin, has been widely used for mitotic stimulation to human lymphocytes, cell arrest, or apoptosis, potential sources for developing novel pharmaceutical preparation and intensive interest for health care services, biologist and phytomedicine research can be considered